Health care use by adults with obesity: A French cohort study. Issue 3 (10th February 2022) - Feral‐Pierssens, Anne‐Laure; Matta, Joane; Rives‐Lange, Claire; Goldberg, Marcel; Zins, Marie; Carette, Claire; Czernichow, Sébastien
Abstract: Objective: Studies on obesity costs have focused on global costs of people with obesity but scarcely investigated their precise use of health care. The aim of this study is to document real‐life health care use across obesity classes. Methods: Data of participants with obesity and enrolled in the CONSTANCES cohort were analyzed. Health care use was defined as ≥1 visit to general practitioners, specialists, emergency departments, and inpatient hospital admissions versus none over a 3‐year period prior to enrollment and was obtained from the Universal Health Insurance database. Multivariate regression models were conducted and adjusted for comorbidities and social deprivation markers with medical visits as the outcome variables and compared people with class II and III obesity versus class I obesity. Results: Out of the 10, 774 participants with obesity, 613 (5.7%) had class III obesity, and 2, 076 (19.3%) had class II obesity. Compared with participants with class I obesity, class III obesity participants had higher odds of visiting emergency departments (OR = 1.31; 95% CI: 1.07‐1.61) and various specialist physicians (pneumologists, endocrinologists, cardiologists) but lower odds of visiting gynecologists (OR = 0.69; 95% CI 0.55‐0.87). Participants with class II obesity had lower odds of visiting general practitioners, dentists, and psychiatrists. There was no difference with regard to hospital admissions. Conclusion: Health care use by people with obesity differs across classes.